2019
DOI: 10.1002/cbdv.201900325
|View full text |Cite|
|
Sign up to set email alerts
|

Pristimerin Induces Autophagy‐Mediated Cell Death in K562 Cells through the ROS/JNK Signaling Pathway

Abstract: Chronic myeloid leukemia (CML) is a lethal malignancy, and the progress toward long‐term survival has stagnated in recent decades. Pristimerin, a quinone methide triterpenoid isolated from the Celastraceae and Hippocrateaceae families, is well‐known to exert potential anticancer activities. In this study, we investigated the effects and the mechanisms of action on CML. We found that pristimerin inhibited cell proliferation of K562 CML cells by causing G1 phase arrest. Furthermore, we demonstrated that pristime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…It is regulated and induced by multiple factors, among which the ROS-JNK pathway is one of the most important 25 . Once activated by ROS, JNK1 can directly phosphorylate Bcl-2 protein and dissociate it from Beclin 1, thereby initiating autophagy 26 , 27 . In addition, the ROS-JNK signaling pathway can induce autophagy by directly upregulating the key autophagy genes autophagy gene 7 (ATG7) and ATG5 through a Beclin1-independent mechanism 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is regulated and induced by multiple factors, among which the ROS-JNK pathway is one of the most important 25 . Once activated by ROS, JNK1 can directly phosphorylate Bcl-2 protein and dissociate it from Beclin 1, thereby initiating autophagy 26 , 27 . In addition, the ROS-JNK signaling pathway can induce autophagy by directly upregulating the key autophagy genes autophagy gene 7 (ATG7) and ATG5 through a Beclin1-independent mechanism 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Siha cells were plated at a density of 1.0×10 6 cells/well into 6-well flat-bottom tissure culture plates and treated with different concentrations of curcumin (30 and 50 µM) or vehicle control DMSO for 24 h, or with Cur 50 µM + NAC. After the treatment, the cells were harvested, washed twice with ice cold PBS (pH 7.4) and fixed in 70% ethanol for overnight at 4 °C.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence has shown that pristimerin treatment gives rise to cell accumulation in G0/G1 phases and cell reduction in S and G2/M phases, indicating the induction of G0/G1 phase arrest to exhibit anti-proliferative effects on various cancers including CRC (22,38), breast cancer (9,21), uveal melanoma (UM) (18,23,30), chronic myelogenous leukemia (CML) (39), oral squamous cell carcinoma (OSCC) (27), esophageal cancer (40), pancreatic cancer (26,41), prostate cancer (24,25) and cholangiocarcinoma (42). However, a study related to the imatinib-resistant CML has found that pristimerin does not significantly affect the cell cycle other than the emergence of cells in the sub-G1 apoptotic phase (43).…”
Section: Alterations In Essential Cellular Events Under Pristimerin Treatment G1 Phase Arrest Inductionmentioning
confidence: 99%